POPULATION STUDIES OF SEA TURTLE IN BA'BATOA LAPEO BEACH POLEWALI MANDAR REGENCY, WEST SULAWESI, INDONESIA - Rini, Indri Putri Sekar; Anggara, Dimas Wahyu; Ardy, Ardy; Ardiansyah, Muh. Putra; Jakasukmana, Munandar; Nurdin, Nur Masyitha; Yudiarso, Permana; Jati, Oktavianto Eko (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2024)
Sea turtles are marine biota that have an important role in the lives of coastal communities, but their existence has decreased due to threats to their habitat. The protection status of sea turtles has been regulated nationally and internationally, where they are fully protected. One location with potential sea turtle habitat in West Sulawesi is Ba'batoa Lapeo Beach in Polewali Mandar Regency. This is evidenced by the existence of community groups that carry out sea turtle conservation activities. This research analyzes the population of landed sea turtles, analyzes the success rate of hatching sea turtle eggs, and identifies threats that occur in efforts to manage sustainable sea turtle conservation at Ba'batoa Lapeo Beach. Data was collected through collaboration between BPSPL Makassar and the Laut Biru Community Group—the implementation of data collection from April to July 2024 through primary and secondary data collection. Primary data is obtained directly from the results of monitoring by the Laut Biru Community Group. Secondary data is used to describe primary data. Based on the analysis results, the type of sea turtle that landed on Ba'batoa Lapeo Beach was the Olive Ridley Turtle (Lepidochelys olivacea) 42 times. The highest percentage of Olive Ridley Sea Turtle eggs hatching was in July 2024 at 95.54%, while the lowest was in April 2024 at 51.45%. Threats to sea turtle habitat in Ba'batoa Lapeo Beach are abrasion and natural predators such as monitor lizards. The results of this study are expected to optimize the national sea turtle database and become a concern for stakeholders for sea turtle conservation management in West Sulawesi Province.